Obtaining of functional surface active monomers based on tert-butylperoxy-6-hydroxyhexanoate - Borzenkov, Mykola; Dolynska, Larysa; Kochubei, Viktoria; Nadashkevich, Zoriana; Hevus, Orest (Publishing House of Lviv Polytechnic National University, 2011)
The interaction of e-caprolactone with tertbutylhydroperoxide led to tert-butylperoxyhexanoate. Peroxymaleinate has been obtained by the reaction of tert-butylperoxyhexanoate with a maleic anhydride. Functional monomers have been synthesized by reactions of peroxymaleinate with propansultone and polyethylene glycol (PEG). The obtained compounds exhibit surface active properties, reducing a surface tension at the water-air interface. При взаємодії e-капролактону з трет-бутилгідропероксидом одержано трет-бутилперокси-6-гідро-ксигексаноат, реакцією якого з малеїновим ангідридом синтезовано пероксидовмісний малеїнат. Взаємодією останнього з пропансультоном і поліетиленгліколем отримано функціональні мономери. Отримані речовини є типовими ПАР і знижують поверхневий натяг на межі вода–повітря.
Синтез функціональних поверхнево-активних мономерів на основі трет-бутилперокси-6-гідроксигексаноату
Keywords: e-caprolactone; peroxides; surface active monomers; surface tension; e-капролактон; пероксиди; поверхнево-активні мономери; поверповерхневий натяг